Workload and Stress: Their Effects on Job Satisfaction at PT. Inhutani I Umi Gresik - Listin Anggraini; Dian Ferriswara; Galuh Ajeng Ayuningtiyas; Anita Asnawi (Harmony Management: International Journal of Management Science and Business, 2025)
This study examines the impact of workload and work stress on employee job satisfaction at PT Inhutani I UMI Gresik, a wood-processing company operating under Perum Perhutani. The research employed a quantitative design with an associative (causal) approach to identify the extent to which workload and stress contribute to variations in job satisfaction. Data were collected through questionnaires distributed to 48 employees selected using a simple random sampling method. The analytical process involved validity and reliability testing, classical assumption tests, multiple linear regression, as well as t-tests, F-tests, and the coefficient of determination (R²). The results indicate that workload and work stress, when considered simultaneously, have a significant influence on job satisfaction. However, partial testing revealed that workload did not exert a significant effect, while work stress had a statistically significant negative impact on satisfaction. Regression analysis further demonstrated that work stress emerged as the dominant predictor, accounting for a larger proportion of variance compared to workload, as reflected by the higher beta coefficient and partial determination value. These findings suggest that while workload may serve as a motivator when maintained within reasonable limits, unmanaged stress arising from role ambiguity, conflicting demands, and organizational pressures significantly undermines job satisfaction. The study underscores the importance of stress management strategies within organizations, particularly in high-demand industries such as forestry and wood processing. Practical implications include the need for supportive leadership, effective communication, realistic target-setting, and the implementation of employee assistance programs. By addressing stress more effectively, organizations can enhance employee well-being, foster greater job satisfaction, and ultimately improve overall organizational performance.